Here Comes The Showboat! - Bryant, Betty, 1922-1999 (Book collections on Project MUSE., 1994)
""I was born at the tail end of a unique and delightful era and raised on one of the last showboats to struggle for survival against the devastating crunch of progress ... Our showboat's express purpose was carrying entertainment to hundreds of thousands of river-bottom farmers along our water-bordered frontier.""--The bookBetty Bryant was a river rat. The Floating Theater was her home, and the river was her back yard. While other children were learning to walk, she was learning to swim. She knew how to set a trotline, gig a frog, catch a crawdad, and strip the mud vein out of a carp by